La incidencia del consumo de sustancias psicoactivas en los asuntos de violencia intrafamiliar reportados a la Comisaría de Familia de Pitalito - Huila, periodo 2016 - 2018 - Cumbe Angel, Javier Orlando (Universidad Antonio Nariño, 2021)
Through this investigation, the statistics of intrafamily violence issues reported to the Family Police Station of the Municipality of Pitalito - Huila, in the period from 2016 to 2018, will be analyzed, in order to determine the incidence of consumption of psychoactive substances in these factual situations that significantly affect the stability of families; looking through a systematic analysis to make recommendations on prevention, care and solution from the family, social and institutional spheres that favor this community.